PJMHS 2022
DOI: 10.53350/pjmhs221611020
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Trial of Combined Surgical and Hormonal Therapy of Endometriosis

Abstract: Aim: To evaluate the three therapy strategies including surgical therapy, hormonal therapy, and combined treatment for the management of endometriosis Study design: A multicentric randomized control trial Place and Duration: This study was conducted in 6 different hospitals of Pakistan, Muhammad Medical and Dental College Ratanabad Mirpurkhas, Social Security Landhi Hospital Karachi, Sindh Government CDF Hospital , Bilawal Medical College for Boys Jamshoro, Ghulam Muhammad Mahar Medical College Sukkur, Bah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In their randomized controlled trial (RCT), Bala et al found no difference between GnRHa, surgery or combined treatment on the CPR or LBR [14]. However, there are uncertainties in the method of randomization, patient demographics and fertility outcomes and firm conclusions cannot be drawn on the basis of this study.…”
Section: Surgical Treatment To Enhance Spontaneous Conceptionmentioning
confidence: 77%
“…In their randomized controlled trial (RCT), Bala et al found no difference between GnRHa, surgery or combined treatment on the CPR or LBR [14]. However, there are uncertainties in the method of randomization, patient demographics and fertility outcomes and firm conclusions cannot be drawn on the basis of this study.…”
Section: Surgical Treatment To Enhance Spontaneous Conceptionmentioning
confidence: 77%